RANCANG BANGUN BALING-BALING TIPE VERTIKAL PEMBANGKIT LISTRIK TENAGA ANGIN DENGAN BAHAN SERAT KELAPA SAWIT KAPASITAS 500 WATT - Jamaludin, Jamaludin; Sumarno, Sumarno; Ardian, M Arief Alfi (Motor Bakar : Jurnal Teknik Mesin, 2024)
Wind energy can be utilized in wind power plants. Wind power generation is a method for generating electrical energy by rotating a wind turbine which is connected to a generator as an electricity generator, then the electrical energy produced by the generator is stored in an electrical energy storage element (battery). The most important part of a Wind Power Plant is in Wind Turbines or commonly called Propellers. The design and manufacture of this propeller uses dried palm oil fiber as a substitute for glass fiber to reduce environmental pollution and utilize waste from palm oil processing. The propellers in this wind power plant (PLTB) are designed in this thesis with the aim of capturing wind which will be converted into electricity. The design of these propellers is taken into account in various aspects, especially in the aspect of the cross-sectional area which has a width of 25 cm and a height of 25 cm. 50 cm. This size produces 68.0945 watts of power at a wind speed of 6.1 m/s.